A colorimetric paper-based sensor for toltrazuril and its metabolites in feed, chicken, and egg samples. (15th March 2019) - Wang, Zhongxing; Zhang, Jian; Liu, Liqiang; Wu, Xiaoling; Kuang, Hua; Xu, Chuanlai; Xu, Liguang
Highlight: A highly sensitive monoclonal antibody has been produced for first time. The proposed assay has cutoff values of <20 μg/kg for Tol and 50 μg/kg for Tol sulfone when evaluated with the naked eye in 15 min. Quantitative results were obtained with a strip scan reader, with limits of detection <2.60 μg/kg for Tol and its metabolites in real samples. This immunoassay can be applied to the high throughput on-site determination of Tol and Tol sulfone in food and agricultural samples. Abstract: In this study, a sensitive monoclonal antibody (mAb) against toltrazuril (Tol) was developed based on a novel hapten. The 50% inhibitory concentrations (IC50 ) of toltrazuril and its metabolites ranged from 2.19 ng/mL to 4.21 ng/mL. Based on this mAb, a colorimetric paper-based sensor was developed for the rapid screening of Tol and its metabolites in samples. The proposed assay has cutoff values of <20 μg/kg for Tol and 50 μg/kg for Tol sulfone when evaluated with the naked eye, and the results could be obtained in 15 min. Quantitative results were obtained with a strip scan reader, with limits of detection <2.60 μg/kg for Tol and its metabolites in real samples. The sensitivity of both qualitative and quantitative detection meets the European Union requirements. Therefore, this strip assay provides a useful tool for the on-site detection and rapid initial screening of Tol and its derivatives in feed, egg, and chicken samples.